Assessment of liquefaction potential and susceptibility during earthquakes in Cebu and Mandaue cities, the Philippines - Ramientos, Cherry Clarissa A.; Bergado, Dennes T.; Balasubramaniam, A.S.; Honjo, Yusuke; Tian Ho Seah; Government of Australia, with Supplementary Research Grant from AIT Alumni Association (AITAA) (Bangkok : Asian Institute of Technology, 1993)
Subsurface data consisting of 153 boreholes were collected from consulting firms and government agencies. These were supplemented with data collected during a field investigations. Subsurface data were analyzed using the Simplified Method and Empirical Method to produce critical acceleration values required to cause liquefaction. Seismicity data derived from government agency was used to established the frequency-magnitude relationship needed to produce the 100 year exceedance probability curve. These critical accelerations were then used to classify each site as having liquefaction potential as high, moderate, low or very low liquefaction susceptibility. These susceptibilities were plotted on base maps to aid in defining liquefaction potential zone. The liquefaction in Dagupan City which was brought about by the 16 July 1990 Luzon earthquake was verified using Simplified Method. Liquefaction occurrence along Magsaysay Bridge and area northwest of Quintos Bridge were confirmed to be liquefiable and not liquefiable areas, respectively. Results from this study indicate that there are soil deposits susceptible to liquefaction within the study areas as shown in the liquefaction potential maps, although their potential for liquefaction is much lower than that of Dagupan City due to lower seismic activities. These liquefaction potential maps produced in this study are intended for local government agencies to mitigate the risk associated with the hazard of soil liquefaction during earthquakes and by individuals involved in developing the areas to aid in the planning of subsurface investigations and the development of zoning guidelines.
A thesis study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1993
Keywords: Soil liquefaction; Earthquakes -- Philippines -- Cebu